Farmers’ Willingness to Pay Bio-Activators to Maintain Soil Fertility - Relawati, Rahayu; Iriany, Aniek; Prihartini, Indah; Ramli, Mona Fairuz (SOCA: Jurnal Sosial Ekonomi Pertanian; Vol 16 No 3 (2022): Vol 16 No 3 (2022)DO - 10.24843/SOCA.2022.v16.i03.p01, 2022)
How farmers are willing to pay bio-activators needs to be studied. The purposes of this study are to analyze the knowledge and use of bio-activators, as well as the willingness to pay for bio-activators in rice farming. The research was conducted in Malang Regency, with a sample of 82 farmers from Ngajum and Gondanglegi Districts. Data were analyzed by descriptive and multiple linear regression. The results showed that the farmers are aware of one to four brands of bio-activators, and three of the brands are used by the rice farmers. The benefits of using bioactivators that are mostly perceived by rice farmers are fertilizing the soil and plants, thereby increasing the production of rice farming. Willingness to pay for bioactivators is based on the prevailing market price, there is no willingness to pay a premium price. Factors that have a positive effect on willingness to pay are land area and benefits of bio-activators. The wider the agricultural land owned by the farmer and the greater the perceived benefits, the greater the value of willingness to pay will be. This information can be taken into consideration for manufacturers of bio-activators as a new introduction before being released in the market.